Analisis Faktor Determinan Fundamental Tax Avoidance Dengan Committee Ratio Sebagai Variable Moderating - Friyan Satria (Universitas Pelita Harapan Medan Campus, 2021)
Abstract: The objective of the research was to analyze the influence of discretionary accrual, income smoothing, effective tax rate, complexity, firm size, firm value, and audit quality as independent variables on tax hindrance and committee ratio as moderating variable. The research object was food and beverages companies listed in the Indonesian Stock Exchange in the period of 2012-2014. The population was 45 companies, and 36 of them were used as the samples. The hypothesis was tested by using multiple linear regression analysis. The result of the research showed that independent variables of discretionary accrual, income smoothing, effective tax rate, complexity, firm size, firm value, and audit quality simultaneously had significant influenced on tax hindrance. Partially, the variables of effective tax rate and firm value had positive and significant influence on tax hindrance, the variable of income smoothing had negative and insignificant influence on tax hindrance, and the variables of discretionary accrual, complexity, firm size, and audit quality had positive and significant influence on tax hindrance. The variable of committee ratio was not a moderating variable.Keywords: Tax Hindrance, Discretionary Accrual, Income Smoothing, Effective Tax Rate, Complexity, Firm Size, Firm Value, Audit Quality, Committee Ratio